Malignant pulmonary neoplasms predisposing to pneumothorax - CICĖNAS, Saulius; VENCEVIČIUS, Vladislavas (Acta medica Lituanica, 2011)
Bachground. The main purpose was to point out pneumothorax (P) as the first symptom of thoracic malignancy. The mechanisms by which pneumothorax occurs in lung cancer are not clear. Materials and methods. From 1970 to 2009, 42 cases of pneumothorax as the initial symptoms of lung cancer were diagnosed at the Department of Thoracic Surgery and Oncology, Institute of Oncology, Vilnius University. In 27 patients (64.3%), pneumothorax occurred in primary lung carcinoma (LC) and 15 patients (35.7%) in metastatic LC. The mean age was 53.7 years. The morphology of LC was as follows: squamous cell carcinoma 17 cases (40.4%), adenocarcinoma 6 cases (14.3%) and small cell carcinoma 5 cases (11.9%). Morphology in the group of 15 metastatic cases (35.7%): 2 cases of metastatic angiosarcoma, 3 cases of chondrosarcoma, 4 cases of seminoma, 4 cases of renal cancer and 2 cases of metastatic synovial sarcoma. Results. Pleural drainage with chemotherapy was used for 16 patients (38.0%), 21 patients (50.0%) underwent thoracotomy, and 5 patients (11.9%) video-assisted thoracic surgery (VATS). Complications were noted in 10 patients (23.8%). Pneumothorax was cured in 41 patients (97.6%), and 1 patient (2.4%) died. In 16 patients (38.0%) the lung was expanded by drainage, 21 (50.0%) underwent surgery and 5 patients (11.9%) minimal invasive surgery (VATS), 14 patients (33.3%) underwent chemoradiation after lung recovery. Median survival of the patients was 31 months. Conclusions. Pneumothorax as the first manifestation of LC appears not often but may have dangerous complications. Keywords: lung cancer, pneumothorax, pneumothorax as an initial symptom of malignant pulmonary neoplasms, diagnostics and treatment of lung cancer, lung metastases